The role of innate immune cells in the pathogenesis of experimental autoimmune encephalomyelitis - Mc Guinness, Niamh (Trinity College. Institute of Neuroscience, 2015)
Experimental autoimmune encephalomyelitis (EAE) is a widely exploited animal model of multiple sclerosis (MS) and is a valuable tool in understanding the cellular and molecular basis of autoimmunity and inflammation in the central nervous system (CNS). Like MS, the primary pathogenic event in EAE is the infiltration of encephalitogenic CD4+ T cells into the brain and spinal cord, particularly autoantigenspecific, IL-17-producing Th17 cells, and IFN-y-producing Thl cells. Once these cells enter the CNS, they mediate damage to axons through targeted destruction of the myelin sheath, and thus contribute to neuronal dysfunction. Recently is has come to light that cells of the innate immune system, such as natural killer (NK) cells, and macrophages, may also play a critical role in the induction of EAE through modulation of the encephalitogenicity of CD4+ T cells.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin.